1997
DOI: 10.1093/oxfordjournals.aje.a009138
|View full text |Cite
|
Sign up to set email alerts
|

Smoking History in Middle Age and Subsequent Cognitive Performance in Elderly Japanese-American Men: The Honolulu-Asia Aging Study

Abstract: The associations between cigarette smoking history and later cognitive performance were examined among 3,429 Japanese-American participants of the Honolulu Heart Program (HHP) and its extension, the Honolulu-Asia Aging Study (HAAS). Cognitive performance was measured by the Cognitive Abilities Screening Instrument (CASI), administered as part of HAAS (mean age at HAAS exam (standard deviation (SD)): 77.7 (4.6) years). Information on smoking history was collected during the first and third HHP exams (mean age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 37 publications
4
55
0
3
Order By: Relevance
“…Similarly, a recent analysis among this cohort indicated that smoking history was less reliably reported by low CASI scorers than by other HAAS participants. 23 Additional strengths of this study include the size of the cohort and the high rates of participation during the follow-up examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a recent analysis among this cohort indicated that smoking history was less reliably reported by low CASI scorers than by other HAAS participants. 23 Additional strengths of this study include the size of the cohort and the high rates of participation during the follow-up examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Terms were entered to describe the smoking history of participants up to Exam III, as this was recently found to be significantly related to cognitive performance in this cohort. 23 …”
Section: Other Covariatesmentioning
confidence: 99%
“…In the Honolulu-Asia study, 92% of the dementia cases diagnosed by DSM IIIR criteria scored Ͻ82 on the CASI. 65 Isolated memory loss was recently documented in the Seattle Dementia Study to be a strong predictor of subsequent clinical dementia; 10 of 21 individuals (48%) with isolated memory loss became clinically demented during a 48-month follow-up period. 66 Verbal memory loss is also an early sign of dementia.…”
Section: Diagnosis Of Dementiamentioning
confidence: 99%
“…Once infected, HIV-seropositive smokers presented a higher serum β2-microglobulin level and an increased CD4 cell count, which lasted approximately 2 years (Royce and Winkelstein, 1990;Burns et al, 1991). Studies performed in the post-HAART era, during which the incidence of opportunistic infections has decreased markedly, have found that smoking is associated with a decreased quality of life and an increased mortality (Page-Shafer et al, 1996;Turner et al, 2001; Crothers et al, smoking presents a higher risk of late-life cognitive impairment (Galanis et al, 1997;Richards et al, 2003). Nonetheless, clinical studies involving nicotine administration in healthy smokers and nonsmokers have shown an enhancement of cognitive function, mostly involving attention and psychomotor speed domains (Sacco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%